AGE-FRIENDLY NEW ENGLAND: CREATING HEALTHY AGING DATA REPORTS TO SPUR SOCIAL CHANGE. (11th November 2018) - Dugan, E; Porell, F; Silverstein, N M; Lee, C; Kim, B; Wang, S; Pitheckoff, N
Abstract: Across New England stakeholders are promoting healthy aging by building age-friendly communities (healthyagingdatareports.org). Each state data report includes community profiles with 120+ indicators of healthy aging at the local community level (MA n=367; RI n=41; NH n=220). Rarely is healthy aging data reported at such a local level. Data from the Centers for Medicare and Medicaid Services, Behavior Risk Factor Surveillance System, US Census and other sources were analyzed using small area estimation techniques to determine age/sex adjusted community rates. Interactive online maps show the distribution of disease and highlight health disparities. Selected results include state rates for MA/RI adults 65+ with: diabetes (32%/36%), hypertension (78%/79%), stroke (13%/13%), Alzheimer's disease or related dementias (14%/14%), depression (29%/30%), and 4+ chronic conditions (59%/64%). Multivariate analyses showed differences in population health and identified modifiable risk factors for community health.